MODIFIKASI MODEL PEMBELAJARAN BAGI ANAK CEREBRAL PALSY (Suatu Tantangan Kreativitas Guru) - Hermanto, Hermanto (MAJALAH ILMIAH PEMBELAJARAN, 2006)
One of special need for children group that is categorized physical handicaps is cerebral palsy strap. The Cerebral Palsy strap is the personal who gets the stiffness that the cause is in the brain. As a CP strap their academic abilities are variety, there's clever and low academic ability. Generally the CP strap get the education opportunity in SLB part D. they follow studying process by the same material with the common children in the same level. Although the lesson material's that is given same, but in teaching the teachers need teaching model modification needs the creativity of support teacher very much. More creative that is according with the children ability, it will more help to make easy the CP strap in following and finishing the lesson material.